El ocaso del título al portador - Rojas Chan, Anayansy (Universidad de Costa Rica - Colegio de Abogados y Abogadas de Costa Rica, 2018)
This article analyzes the latest technological events, regulatory provisions, and the underlying basis that have driven financial institutions --such as security issuers--to eliminate the use of bearer bonds in Costa Rica due to pragmatic reasons. The anonymous nature of the bearer bond has gradually become an obstacle to the huge local and international need to fight money laundering and tax evasion, which are all circumstances that led to its inevitable elimination.